1993
DOI: 10.1002/bjs.1800800224
|View full text |Cite
|
Sign up to set email alerts
|

Changes in major histocompatibility complex class II expression in monocytes and T cells of patients developing infection after surgery

Abstract: Expression of class II major histocompatibility complex (MHC) on monocytes is a prerequisite for effective antigen presentation and processing, an important component of the immune response to infection. It has been reported that the level of monocyte class II expression may identify patients who go on to develop infective complications following trauma. In the present study, flow cytometry was used to measure MHC class II (human leucocyte antigen (HLA)-DR) expression on circulating monocytes and T cells in 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
2
9

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(155 citation statements)
references
References 27 publications
10
134
2
9
Order By: Relevance
“…While decreased monocyte HLA-DR expression can be associated with increased infection rates or poor outcome in major surgery or trauma [9][10][11][12][13], we observed a substantial degree of HLA-DR reduction in our patients, whose risk of developing postoperative complications was lower than the complex major surgery previously studied. Delayed recovery of HLA-DR depression (i.e.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…While decreased monocyte HLA-DR expression can be associated with increased infection rates or poor outcome in major surgery or trauma [9][10][11][12][13], we observed a substantial degree of HLA-DR reduction in our patients, whose risk of developing postoperative complications was lower than the complex major surgery previously studied. Delayed recovery of HLA-DR depression (i.e.…”
Section: Discussioncontrasting
confidence: 54%
“…Human Leukocyte Antigen-DR (HLA-DR), one of the Major Histocompatibility Complex class-II proteins expressed on monocytes, macrophages and dendritic cells, is a crucial molecule for the presentation of antigen to lymphocytes and the initiation of adaptive immune responses [7,8]. Reduced levels of HLA-DR expression on blood monocytes following surgery is proposed as a potential biomarker for surgeryinduced immunosuppression and the development of postoperative infections [7,[9][10][11][12][13]. However, previous studies have focused on high risk surgery, trauma or sepsis.…”
mentioning
confidence: 99%
“…On admission the mean age of the trauma patients ( n = 31) was 32路8 (range, 18-59), the mean ISS was 32路0 (17-59), APACHE II score of 13路5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and mean GCS of 8路7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). There were 25 men and six women.…”
Section: Resultsmentioning
confidence: 99%
“…1 day after the traumatic event, was evaluated by assessment of HLA-DR expression on monocytes, a parameter known to correlate with clinical outcome in diverse populations [7][8][9][10][11][12]. In addition, the proliferative capacity of T cells and cytokine production profile upon mitogenic stimulation were evaluated, because T cells are essential for a primary immune response and were reported to be functionally compromised in traumatized patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the decrease of mHLA-DR expression has mainly been assessed as a predictor of septic complications after trauma, surgery, or pancreatitis (28,(92)(93)(94)(95)(96)(97)(98). In these studies, low levels of mHLA-DR (<40% of positive monocytes, normal >90%) were observed in patients who subsequently developed nosocomial infections.…”
Section: Mhla-dr Expression and Clinical Studymentioning
confidence: 99%